Binding of direct oral anticoagulants to the FA1 site of human serum albumin. Issue 3 (9th October 2020) - De Simone, Giovanna; Pasquadibisceglie, Andrea; di Masi, Alessandra; Buzzelli, Valeria; Trezza, Viviana; Macari, Gabriele; Polticelli, Fabio; Ascenzi, Paolo
Abstract: The anticoagulant therapy is widely used to prevent and treat thromboembolic events. Until the last decade, vitamin K antagonists were the only available oral anticoagulants; recently, direct oral anticoagulants (DOACs) have been developed. Since 55% to 95% of DOACs are bound to plasma proteins, the in silico docking and ligand‐binding properties of drugs apixaban, betrixaban, dabigatran, edoxaban, and rivaroxaban and of the prodrug dabigatran etexilate to human serum albumin (HSA), the most abundant plasma protein, have been investigated. DOACs bind to the fatty acid (FA) site 1 (FA1) of ligand‐free HSA, whereas they bind to the FA8 and FA9 sites of heme‐Fe(III)‐ and myristic acid‐bound HSA. DOACs binding to the FA1 site of ligand‐free HSA has been validated by competitive inhibition of heme‐Fe(III) recognition. Values of the dissociation equilibrium constant for DOACs binding to the FA1 site (ie, calc K DOAC ) derived from in silico docking simulations (ranging between 1.2 × 10 −8 M and 1.4 × 10 −6 M) agree with those determined experimentally from competitive inhibition of heme‐Fe(III) binding (ie, exp K DOAC ; ranging between 2.5 × 10 −7 M and 2.2 × 10 −6 M). In addition, this study highlights the inequivalence of rivaroxaban binding to mammalian serum albumin. Given the HSA concentration in vivo ( 7.5 × 10 −4 M), values of K DOAC here determined indicate that the formation of the HSA:DOACs complexes in the absence and presence of FAs and heme‐Fe(III) may occur in vivo. Therefore, HSA appears to be an important determinant for DOACs transport. Abstract : Binding of direct oral anticoagulants to the FA1 site of human serum albumin